2022
DOI: 10.1093/procel/pwac008
|View full text |Cite
|
Sign up to set email alerts
|

A molecular brake that modulates spliceosome pausing at detained introns contributes to neurodegeneration

Abstract: Emerging evidence suggests that intron-detaining transcripts (IDTs) are a nucleus-detained and polyadenylated mRNA pool for cell to quickly and effectively respond to environmental stimuli and stress. However, the underlying mechanisms of detained intron (DI) splicing are still largely unknown. Here, we suggest that post-transcriptional DI splicing is paused at the B act state, an active spliceosome but not catalytically primed, which depends on Smad Nuclear Interacting Protein 1 (SNIP1) and RNPS1 (a serine-ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Dysplasia and caspase 9-dependent apoptosis were significantly upregulated in the brain lacking SNIP1. SNIP1 exerts mechanistic control over target genes that promote cell viability and neurogenesis [ 42 ]. The functionality of SNIP1 is influenced by the TGFβ and NF-κB signaling pathways.…”
Section: Application Of Snip1 In Clinical Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Dysplasia and caspase 9-dependent apoptosis were significantly upregulated in the brain lacking SNIP1. SNIP1 exerts mechanistic control over target genes that promote cell viability and neurogenesis [ 42 ]. The functionality of SNIP1 is influenced by the TGFβ and NF-κB signaling pathways.…”
Section: Application Of Snip1 In Clinical Diseasesmentioning
confidence: 99%
“…Scholars have observed that SNIP1 facilitates neurogenesis and inhibits cell death in the murine brain development model. Further investigations have also implicated SNIP1 in the prevention of cell death [ 42 , 43 ]. Moreover, the presence of SNIP1 has been found to enhance the interaction between the Polycomb complex PRC2 and the genome, leading to the removal of H3K27me3 from specific target genes [ 44 ].…”
Section: Application Of Snip1 In Clinical Diseasesmentioning
confidence: 99%
See 2 more Smart Citations